ANALISIS PROBLEMATIKA MANAJEMEN INVESTASI WAKAF UANG PADA LEMBAGA WAKAF UANG DI SUMATERA BARAT (STUDI PENDEKATAN ANALITICAL NETWORK PROCCESS) - Firdaus, Nil; Nuruddin, Amiur; Hasmawati, Fifi (JURIS (Jurnal Ilmiah Syariah), 2019)
Cash Waqf is an endowment done by a person, group, institution or legal entity in the form of cash where the purpose is for the welfare of the community. This study aims to determine the priority of problems, solutions and stategies of investment management through the Analytical Network (ANP) approach. The results showed the priority of the problem was Nazhir's professionalism (0.407) risk analysis (0.247) supervision (0.205) and guarantee (0.140) with the rater agreement (W: 0.619). Priority solutions are Nazir?s professionalism (0.408) supervision (0.239) risk analysis (0.213) and guarantee solutions (0.138) with rater agreement (W: 0.555). While the strategy priority is cooperation with tungku tigo sajarangan (0,366) public education (0,324) and nazhir coaching (0,308) with rater agreement (W: 0,111).